Society and Culture of Cambodia in the Angkorian Period under the influence of Buddhism (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purposes of this article were 1) to present the society and culture of Cambodia in the Angkorian period, 2) to discover Buddhism in the Angkorian period, and) to analyze the influence of Buddhism on the society and culture of Cambodia in the Angkorian period. This relies on the primary source of data used in the documentary research. The methodology adopted in the study is of a critical and investigative approach to the analysis of data gathered from documentary sources. The result indicated that: ancient Cambodia inherited civilization from India. The ancient Cambodians, therefore, respected both Brahmin and Buddhism. The Cambodian way of life in the Angkorian era was primarily agricultural occupation, and the monarchy was the ultimate leader. Buddhism has spread in Cambodia after the finishing of the 3rd Buddhist Council. The king accepted Buddhism as the Code of conduct and carried on for a period. Mahayana Buddhism was the main school in this period. King Jayavarman VII was one of the kings in this period. In this period, the Jayavarman VII has changed the Hindu worldview of “Deva-raja” to “Buddha-raja” instead. The influence of Buddhism in this era is in the field of society. One hundred two hospitals have been built, Arogayasala 121 places. The Dhammasala is a public shelter along the way, and the property is donated to the monks and the poor. In culture’s dimension, it consisting of 1) In the architectural aspect such as Bayon castle, Angkor Thom castle, Ta Phrom castle, etc. 2) he building of the 20, 400 Buddha’s statues made of silver, bronze, stone, and to distribute in the kingdom. Also, important Buddha statues have been established and passed on to be enshrined throughout the kingdom, including Thailand today, such as Suphanburi, Ratchaburi, Singburi, and Lopburi, etc. It was Cambodia’s golden age.